Transformation Leadership Model In Improving The Literature Culture Of Santri In PP Al-Bidayah Jember - Yuliani, Bustanul; Arif, Shaifudin; Kuswoyo, Kuswoyo (IAIN PONOROGO, 2023)
Literacy culture in pesantren is a process of habituation to reading and writing. This activity is a requirement for students as a provision for learning at the pesantren. It takes a strong and visionary transformation paradigm so that it can lead the institution to be born as an institution that has a strong advantage in a particular discipline or field. This kind of indicator was found by the caregivers of the PP Al-Bidayah in Jember in offering a specification of literacy advantages in reading the kitab kuning with various supporting literature. One of the interesting things that the researcher heard and found was the statement he always echoed to the students, namely